Exploitation of European Union Framework Programme results in food, health and wellbeing by small‐ and medium‐sized enterprises: The ‘Quantify Life – Feed Yourself’ (QuaLiFY) project. - Astley, S.; the QuaLiFY consortium (Nutrition Bulletin, 2018)
Abstract: Many European Union Framework Programme‐funded projects and networks have developed tools, knowledge and data that are not being exploited to their full potential. Quantify Life – Feed Yourself (QuaLiFY) sought to capitalise on these resources by making them available to small‐ and medium‐sized enterprises delivering personalised dietary advice services to consumers directly or via healthcare. This study describes how QuaLiFY supported the development of scientifically validated, personalised dietary advice tools and services through development of a federated information and communication technology infrastructure (Quisper), based on open source coding, and tested personalised dietary advice approaches amongst target groups, including overweight young people and dietitians supporting people with type 2 diabetes.